A Scoping Review of Language Programs and Policies in ASEAN Countries - Pugong, Alexee Jaezhelle C.; Pelila, John Rey Osben; Moling, Matin Evony P.; Dolo, Jocel T.; Usman, Norhana A. (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Understanding the socio-economic and cultural impacts of successful language programs on communities is crucial for informed policy decisions. This study aimed to identify the challenges faced by all ASEAN countries and understand the respective policies and programs they are implementing to address these challenges. We conducted a scoping review, reviewing 178 pieces of literature from various databases and websites, based on the identified inclusion criteria. The researchers used profiling and thematic analysis to pinpoint six language-related issues in the ASEAN countries, as well as the implementation of 24 language programs and policies. The study emphasizes the importance of government involvement in language program success, leading to recommendations for a comparative analysis of language education policies, qualitative investigations into stakeholder perspectives, long-term tracking of program outcomes, and in-depth case studies of both successful and unsuccessful programs. Further research should investigate the specific strategies governments employ for successful language program implementation, such as budget allocation, balancing language promotion, and curriculum improvements. Although this study contributes to the broader discourse on language policy, it emphasizes the significance of tailored strategies to address challenges and enhance language education in the ASEAN region.